2013
DOI: 10.1155/2013/394316
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 +1923C/T Polymorphism Is Associated with Asthma Risk: A Meta-Analysis

Abstract: There are controversies on the association between interleukin-13 (IL-13) +1923C/T polymorphism (rs1295686) and the risk of asthma. We performed this study to assess the association by the method of meta-analysis. A systematic search current to October 16, 2012, was conducted using PubMed, EMBASE, and China National Knowledge Infrastructure (CNKI) and identified ten studies comprising 13698 cases and 38209 controls. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. There was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Furthermore, the TT, CT and CC genotypes in asthma group were all significantly associated with increased IgE levels in sera of asthma patients when compared with controls. Our result was consistent with previous meta-analysis conducted by Liu et al [ 54 ], which contained ten included studies and suggested that IL-13 +1923C/T polymorphism was a risk factor for asthma.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the TT, CT and CC genotypes in asthma group were all significantly associated with increased IgE levels in sera of asthma patients when compared with controls. Our result was consistent with previous meta-analysis conducted by Liu et al [ 54 ], which contained ten included studies and suggested that IL-13 +1923C/T polymorphism was a risk factor for asthma.…”
Section: Discussionsupporting
confidence: 93%
“…The IL-13 variant was unable to engage T cells, which suggests that increased allergic inflammation in carriers of IL13 rs20541 A depends on enhanced IL-13-mediated Th2 effector functions rather than increased Th2 differentiation. A recent meta-analysis found that the IL13 +1923C/T polymorphism was significantly associated with the risk of asthma; however, the authors were not able to study the effect of modification by atopic status [25]. The IL13-RAD50 and IL4-KIF3A loci were found to be associated with AR and asthma [9].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we included 25 case-control studies with specific information about the relationship between the +2044A/G and +1923C/T polymorphisms in IL-13 and asthma in a meta-analysis. Although 4 meta-analyses have revealed evidence that these 2 polymorphisms are associated with significantly increased risk of asthma in overall analyses, [ 8 11 ] none reported the relationship between these polymorphisms within specific Asian age groups and atopic status. Wang et al [ 10 ] did not analyze whether +2044A/G was associated with Asian ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although +2044G/A polymorphisms have been correlated with asthma susceptibility in several studies, [ 8 10 ] neither the influences of age nor Asian populations have been described. One study [ 11 ] reported a relationship between +1923C/T polymorphisms and asthma susceptibility; however, the influences of atopic phenotypes and age were not analyzed in Asians. Thus, pooled analysis of all available studies is necessary.…”
Section: Introductionmentioning
confidence: 99%